Diagnóstico dos impactos ambientais da Bacia hidrográfica do Rio Muzambo em Muzambinho-MG - Domingos, Otávio Henrique (2013)
Due to the increase in world population and, consequently, the growing demand for food, agriculture is becoming increasingly essential for the maintenance of life and for the eradication of hunger. Seeking to meet these demands, agriculture has acquired larger proportions, which often culminate in negative environmental impacts resulted from this activity. A natural resource most affected by the disorderly expansion of agriculture are water resources. This paper makes a diagnosis on agricultural activities and environmental impacts from this activity on Muzambo River basin in the town of Muzambinho - Minas Gerais, assessing descriptively the intensity of the impacts whose data are analyzed qualitatively and quantitatively. In this context, we evaluate the anthropogenic influence on the local environment through the characterization of agricultural and domestic activities accomplished in the region, and similarly, we characterized the impacts caused by these activities. It was observed that environmental degradation affected both agricultural areas and areas with natural vegetation, and that there is no adoption of mitigating measures of impacts in the studied area. The control of rainfall runoff, revitalization of riparian forests and proper disposal of solid waste and wastewater are practices that are essential to promote the development of a sustainable agriculture.